Stubbehandling med pergamentsvamp och urea mot sporinfektioner av rotticka i bestånd av hybridlärk - Pålsson, Henrik (SLU/Southern Swedish Forest Research Centre, 2009)
Root rot is a big hurter and a huge economic problem for the Swedish and European forestry. The severest hurter is Heterobasidion annosum (Fr.) Bref and it occurs as two different species in Sweden. Commonly referred to as the P-type (Heterobasidion annosum s.s. (Fr.) Bref.) and the S-type (Heterobasidion parviporum Niemelä & Korhonen). Therefore a lot of research has been carried out in this topic to find a solution and reduce this problem, one alternative that have shown to be profitable is stump treatment in thinnings. Stump treatment is in the present situation a common method to reduce the infections from Heterobasidion annosum in stands mainly dominated by Norway spruce (Picea abies (L.) Karst.). Previously studies show that stump treatment with Rotstop® S and urea gives effective protection against Heterobasidion annosum in stands with mainly spruce. The Forestry in Sweden is today very dependent on tree species as Norway spruce and Scots pine (Pinus sylvestris), but in recent years the interest for other species has grown. One tree species that has become very interesting is hybrid larch (Larix × eurolepis Henry.), regarded as a fast growing species. Hybrid larch don’t differ from spruce when it comes to Heterobasidion annosum, it gets sever damages as well.